Evidence for a decline of PCBs and PAHs in rural vegetation and air in the United Kingdom - Jones, K. C.; Sanders, G.; Wild, S. R.; Burnett, V.; Johnston, A. E. (Nature (London), 1992)
RELIABLE data on persistent organic contaminants in the environment are needed to evaluate strategies to limit their dispersal. Long-term data are often not available, however, because the chemicals in question were not routinely analysed in the past. Although attempts have been made to assess temporal trends by analysis of environmental samples deposited in discrete or identifiable layers (in sediment or peat cores) 1–3 , these media may be disturbed in situ or give poor temporal resolution, or the contaminants may be subject to post-depositional changes. Polychlorinated biphenyls (PCBs) and polyaromatic hydrocarbons (PAHs) are persistent and toxic 4–9 contaminants for which no long-term global ambient monitoring data exist. Plant foliage is a reliable monitor of ambient levels of vapour-phase compounds in air 10–16 and here we present an analysis of archived herbage samples (1965–89) which shows that air concentrations of lower chlorinated PCBs in rural England have decreased by up to a factor of 50 between 1965–69 and 1985–89. High-molecular-weight PCBs and PAHs have also decreased in concentration, but not to such a great extent.